2020
DOI: 10.1111/aej.12444
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic treatment of dentin dysplasia type I D

Abstract: Dentin dysplasia (DD) Type I is a developmental condition affecting dentin, inherited in an autosomal‐dominant pattern or occurring due to a new mutation. Whilst the crowns of DD Type I affected teeth appear clinically normal, the roots are blunt and shortened. Pulp necrosis and periapical pathoses may be seen in the absence of obvious causes. Pulp stones and calcifications are frequently encountered. Endodontic management of DD may be challenging. A case of DD Type I, sub‐classification d, in which spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…24 Comparatively, usage was lower among GDPs surveyed in Malaysia (23.4%) 5 and Denmark (69%), 7 but higher in South Africa (96%). 6 The use of EAL by Group D was also high in this study, similar to or higher than GDPs surveyed in Malaysia, 5 New Zealand, 17 Denmark, 7 the USA, 21 Iran 67 and the UK. 68 Group E's high EAL usage was similar to endodontists surveyed recently in Nepal 69 and the UK.…”
Section: Adoption Of Endodontic Technologiessupporting
confidence: 70%
See 3 more Smart Citations
“…24 Comparatively, usage was lower among GDPs surveyed in Malaysia (23.4%) 5 and Denmark (69%), 7 but higher in South Africa (96%). 6 The use of EAL by Group D was also high in this study, similar to or higher than GDPs surveyed in Malaysia, 5 New Zealand, 17 Denmark, 7 the USA, 21 Iran 67 and the UK. 68 Group E's high EAL usage was similar to endodontists surveyed recently in Nepal 69 and the UK.…”
Section: Adoption Of Endodontic Technologiessupporting
confidence: 70%
“…This study demonstrated the continued uptake of endodontic technologies compared with previous surveys, although usage varied geographically. In this study, 86.3% of Group D used loupes and 5.8% used the DOM, higher than, respectively, 33% and 6% in South Africa, 6 75% and 2% in the USA, 21 7.4% and 1.2% in Malaysia, 5 and 17.1% and 3.2% in Turkey 18 …”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Among non‐endodontic respondents in this survey, on‐site access (25.9%) was also higher than in surveys of general dentists in the Netherlands (8.4%) (van der Zande et al., 2015) and New Zealand (12.3%) (van der Zande et al., 2018). The usage of CBCT for any dental indication in this group (45.4%) was higher than reported in previous studies in Lithuania (17.3%) (Masyte et al., 2021), New Zealand (18.2%) (Loch et al., 2019), South Africa (4%) (Buchanan et al., 2019) and Malaysia (1.6%) (Wong et al., 2019).…”
Section: Discussioncontrasting
confidence: 54%